CONCEPT ANALYSIS OF ADHERENCE TO ANTIRETROVIRAL THERAPY IN PEOPLE LIVING WITH HIV/AIDS - Zahra, Anggri Noorana; Waluyo, Agung; Yona, Sri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
HIV/AIDS remains a global health challenge, with adherence to antiretroviral therapy (ART) being crucial for its management. This comprehensive concept analysis explores adherence to ART in people living with HIV/AIDS, considering its multifaceted nature and the diverse factors influencing it. The purpose of this study was to explore the concept of adherence and define the operational definition of adherence to antiretroviral therapy in PLWH. Walker and Avant’s eight-step concept analysis was used in this study. The terms "adherence", "compliance", "concordance", and "definition" were used in a literature search that was done using the EBSCOhost, Proquest, Science Direct, and Google Scholar databases. The inclusion criteria were full text, written in English or Indonesian, and open access. This study identified four attributes that constitute the concept of adherence: the ability to follow recommended treatment recommendations, collaborative/cooperative whether forced or not, obedience/loyalty/discipline, adaptability and flexibility. The antecedents of adherence to ARV are patient-related factors, therapy-related factors, environment-related factors and health care system-related factors. The consequences of adherence are increasing health outcomes, reducing the transmission of HIV and health care costs. This concept analysis provides a comprehensive understanding of adherence, emphasizing the need for individualized assessments, patient education, stigma reduction, social support, and targeted interventions. Collaboration among healthcare providers, continuous education, and measurement tool refinement are essential for enhancing adherence rates, improving patient outcomes, and reducing the global burden of HIV/AIDS.